2013
DOI: 10.1155/2013/852395
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in the Immunodiagnosis and Outcome of Kidney Allograft Rejection

Abstract: Acute rejection (AR) is responsible for up to 12% of graft loss with the highest risk generally occurring during the first six months after transplantation. AR may be broadly classified into humoral as well as cellular rejection. Cellular rejection develops when donor alloantigens, presented by antigen-presenting cells (APCs) through class I or class II HLA molecules, activate the immune response against the allograft, resulting in activation of naive T cells that differentiate into subsets including cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
13
0
3
Order By: Relevance
“…Glucocorticoid treatment tilts the balance in favor of grafttolerance by promoting the regulatory [Foxp3+ CD4+ CD25+] T-cells while inhibiting the cytotoxicity of T-effector cells [65,66]. Similarly, compared with the staining for IL-17 cytokines, individuals with renal histological specimen that expresses FOXP3 had lower frequency of steroid-resistant rejection events [66,67].…”
Section: Steroid and Allograft Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoid treatment tilts the balance in favor of grafttolerance by promoting the regulatory [Foxp3+ CD4+ CD25+] T-cells while inhibiting the cytotoxicity of T-effector cells [65,66]. Similarly, compared with the staining for IL-17 cytokines, individuals with renal histological specimen that expresses FOXP3 had lower frequency of steroid-resistant rejection events [66,67].…”
Section: Steroid and Allograft Tolerancementioning
confidence: 99%
“…Glucocorticoid treatment tilts the balance in favor of grafttolerance by promoting the regulatory [Foxp3+ CD4+ CD25+] T-cells while inhibiting the cytotoxicity of T-effector cells [65,66]. Similarly, compared with the staining for IL-17 cytokines, individuals with renal histological specimen that expresses FOXP3 had lower frequency of steroid-resistant rejection events [66,67]. In addition, maintenance dose of steroids after a successful treatment of an acute rejection with pulse GC therapy results in a lower occurrence of a Inside the cell, maximum interaction with cytosolic glucocorticoid receptor (GR) occurs with the binding to a complex of chaperones that include immunophilin binding protein (FK506-BP) and heat shock proteins (HSP).…”
Section: Steroid and Allograft Tolerancementioning
confidence: 99%
“…However, vasculitis is not specific to antibodies, as T-cell-mediated immunity can also be an underlying cause of this lesion in bowel allograft vessels. This rejection is the result of effectorimmune T-cell populations being in greater scale and function than the regulatory T-cell populations [46] that suppress ACR. Larger vessel vasculitis is typically identified in explants or rejected organs or autopsies.…”
Section: Hyperacute and Accelerated Acute Rejectionmentioning
confidence: 99%
“…Regulatory T cells (Treg) are involved in inhibiting T cell activation and in developing immune tolerance against autoimmune diseases, tumors, and allografts (Whibley and Gaffen, 2014;Kumar and Subramaniyam, 2015). T helper 17 and Treg cells mutually restrict each other in the body, which helps maintain immune homeostasis (Franzese et al, 2013;Shan et al, 2015). Previous studies have shown that Tregs level was reduced in IgAN patients, which lead to their weakened ability to suppress immune responses.…”
Section: Introductionmentioning
confidence: 99%